2002
DOI: 10.2460/ajvr.2002.63.927
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic characteristics and tissue residues for marbofloxacin and its metabolite N-desmethyl-marbofloxacin in broiler chickens

Abstract: Analysis of pharmacokinetic data obtained in this study reveals that a minimal therapeutic dose of 2 mg/kg, PO, every 24 hours should be appropriate for control of most infections in chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
65
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 37 publications
16
65
7
Order By: Relevance
“…At all tested times post-treatment, marbofloxacin residues were probably higher in the kidneys than other examined tissues. This finding is in agreement with Ding et al [10] and Anadon et al [16] who reported that marbofloxacin concentration in kidney was more than that in liver. But is contrast with Ligabue et al [17] and Yang et al [19] who reported that marbofloxacin concentration in liver was more than that in kidney.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…At all tested times post-treatment, marbofloxacin residues were probably higher in the kidneys than other examined tissues. This finding is in agreement with Ding et al [10] and Anadon et al [16] who reported that marbofloxacin concentration in kidney was more than that in liver. But is contrast with Ligabue et al [17] and Yang et al [19] who reported that marbofloxacin concentration in liver was more than that in kidney.…”
Section: Discussionsupporting
confidence: 83%
“…The results obtained in the present study confirmed that the absorption and distribution of marbofloxacin administered to rabbits via intramuscular injection reach high levels in a short time in kidney, liver, lung and muscle which were in agreement with the previous reports [10, 16,17,19]. Marbofloxacin remained within the detectable limit till the 5 th day in most tested tissues, while in kidney it remained till the 7 th day following last administration of the drug.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This covers MIC 90 value of 0.125-0.20 g/mL against most common E. coli and other gram-negative bacterial infections except P. aeurgenosa in chickens and other birds (Spreng et al, 1995;Haritova et al, 2006 (Anadon et al, 2002). Findings of present study, indicated that the drug was rapidly distributed in the body fluids and then relatively slowly eliminated from the body in broiler chickens after single and repeated i.v.…”
Section: Resultsmentioning
confidence: 55%
“…After single i.v. administration, proximate values of t 1/2β of 5.26  0.66h has been reported in broiler chickens (Anadon et al, 2002) and6.4  0.08 h in foals (Tohamy and El-Gendy, 2013). Whereas, lower values of t 1/2β were found (1.47 ± 0.31 h) in ostriches (De Lucas et al, 2005), (2.83 ± 0.28 h) Muscovy ducks (Goudah and Hasabelnaby, 2010), and (4.03 ± 0.08 h) Japanese quails (Aboubakr and Abdelazem, 2015).…”
Section: Resultsmentioning
confidence: 99%